Генезис структур и предпосылки усовершенствования трансформаторов и реакторов преобразованием контуров электромагнитных систем (системы с шихтованными и витыми магнитопроводами) - Ставинский, А.А. (Електротехніка і електромеханіка, 2011)
Feasibility of transformers and reactors improvement on the basis of spatial structures of axial and radial electromagnetic systems, as well as hexagonal and octahedral generatrix contours of winding coils and cross-sections of laminated and twisted magnetic circuits bars is shown.